2005
DOI: 10.1128/mcb.25.18.8299-8310.2005
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Ablation of the Abcc6 Gene Results in Ectopic Mineralization of Connective Tissues

Abstract: Pseudoxanthoma elasticum (PXE), characterized by connective tissue mineralization of the skin, eyes, and cardiovascular system, is caused by mutations in the ABCC6 gene. ABCC6 encodes multidrug resistanceassociated protein 6 (MRP6), which is expressed primarily in the liver and kidneys. Mechanisms producing ectopic mineralization as a result of these mutations remain unclear. To elucidate this complex disease, a transgenic mouse was generated by targeted ablation of the mouse Abcc6 gene. Abcc6 null mice were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
265
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(281 citation statements)
references
References 64 publications
16
265
0
Order By: Relevance
“…Using transient transfection assays, we defined a proximal promoter for the murine Abcc6 promoter within 152bp upstream from the translation start. In addition, we found that this proximal region conferred high liver-and kidney-specific levels of expression but not in fibroblasts, which is consistent with the in vivo ABCC6/Abcc6 expression profile [39]. In the human sequence, a similar proximal region of the ABCC6 promoter containing a GC-rich domain was defined as conferring tissue specificity and a potential target for transcription factors [28].…”
Section: Discussionsupporting
confidence: 63%
“…Using transient transfection assays, we defined a proximal promoter for the murine Abcc6 promoter within 152bp upstream from the translation start. In addition, we found that this proximal region conferred high liver-and kidney-specific levels of expression but not in fibroblasts, which is consistent with the in vivo ABCC6/Abcc6 expression profile [39]. In the human sequence, a similar proximal region of the ABCC6 promoter containing a GC-rich domain was defined as conferring tissue specificity and a potential target for transcription factors [28].…”
Section: Discussionsupporting
confidence: 63%
“…To date, Ϸ50 mutations of Abcc6 have been found in humans with the autosomal recessive disease, pseudoxanthoma elasticum (PXE), manifested by dystrophic calcification affecting the elastic fibers in skin, Bruch's membrane, and vessel walls with highly variable clinical manifestations (25). It is noteworthy that myocardial calcification has not been reported as a phenotype associated with either human PXE or the mouse Abcc6 knockout models (26,27). Moreover, Abcc6 knockout mice on a B6 background develop medial vascular calcification spontaneously with age, whereas the Abcc6-deficient C3H mice do not show signs of vascular calcification until challenged by hyperlipidemia (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Abcc6 −/− mice faithfully recapitulate most of the symptoms of PXE and have been indispensable for showing that PXE is a metabolic disease (13)(14)(15)(16). Abcc6 −/− muzzle skin that mineralizes in Abcc6 −/− mice does not mineralize when grafted onto WT mice, and muzzle skin of WT mice mineralizes only when grafted onto Abcc6 −/− mice (17).…”
mentioning
confidence: 99%